Phytochemical and Cytotoxic Evaluation of Krangean Fruits Extracts Against HeLa, MCF-7, and HepG2 Cancer Cell Line - Yuli Widiyastuti; Ika Yanti Marfuatush Sholikhah; Sari Haryanti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Krangean [Litsea cubeba (Lour.) Pers.] is one of ancient aromatic plants in Indonesia which is used as traditional medicines such as for carminative, stimulant, stomach ache and expectorant. Otherwise, the anticancer activity of this plant has not been explored extensively. This research aimed to investigate phytochemical content and cytotoxic activity of krangean fruits extract on human cancer cell line in vitro. The research was an in vitro experimental design and the cytotoxic activity was carried out with MMT assay.Â The phytochemical compounds were characterized by TLC (Thin Layer Chromatography). MTT assay was done to observe morphology and viability of HeLa cervical cancer, MCF-7 breast cancer, and HepG2 liver cancer cell line. The results showed that TLC characterization of chloroform and methanolic extracts of Litsea cubeba revealed similar profile, with the major compound found were terpenoid and alkaloid. The MTT assay found that both extracts had strong inhibition on HeLa cell line. Chloroform extract exhibited stronger cytotoxic activities compared to methanol, with the IC50 values of 37.3 and 64.7 Î¼g/mL respectively. While, the both extract have moderate cytotoxic activities to HepG2 and MCF-7 cancer cell line indicated by IC50value more than 100 mg/mL. The benefit of this study is to provide the scientific information regarding the potency of krangean fruit as herbal natural medicine for cervical cancer therapy.